Prevalence of Warfarin Genotype Polymorphisms in Patients with Mechanical Circulatory Support. Issue 4 (July 2015) - Awad, Morcos; Czer, Lawrence S. C.; Soliman, Camelia; Mirocha, James; Ruzza, Andrea; Pinzas, Joshua; Rihbany, Kelsey; Chang, David; Moriguchi, Jaime; Ramzy, Danny; Esmailian, Fardad; Kobashigawa, Jon; et al.
Abstract : Polymorphisms for VKORC1 and CYP2C9 are associated with increased warfarin sensitivity. The prevalence of these polymorphisms in patients with mechanical circulatory support (MCS) is unknown. Polymorphisms for VKORC1 and CYP2C9 were determined in 65 patients undergoing MCS surgery. Postoperative warfarin dose, international normalized ratio (INR), and bleeding events were measured until discharge, 6 months, or composite end point (in-hospital MCS recovery, heart transplant, or death). A total of 67.7% (44/65) had at least one polymorphism: VKORC1 (44.6%), CYP2C9*2 (7.7%), CYP2C9*3 (4.6%), CYP2C9*2 and VKORC1 (3.1%), or CYP2C9*3 and VKORC1 (7.7%). At discharge or before composite end point, patients with any polymorphism received a lower mean warfarin dosage than patients having no polymorphism (3.21 ± 1.47 vs . 5.57 ± 3.72 mg, p = 0.015) and achieved a similar mean INR (2.20 ± 0.67 vs . 2.19 ± 0.69, p = 0.96). There was no significant difference in bleeding rates within 6 months or before composite end point (6.13 vs . 8.02 events/patient-year, p = 0.13). One or more polymorphisms for VKORC1 or CYP2C9 (associated with warfarin sensitivity) were found in 67.7% of MCS patients. By using a warfarin genotype-guided approach, MCS patients with polymorphisms received a lower warfarin dosage to achieve a similar INR, with similar bleeding rates, in comparison with no polymorphisms. A warfarin genotype-guided approach avoided excessive anticoagulation and its attendant bleeding risks.